Photorespiration is crucial for salinity acclimation in castor bean - Ziotti, Ana B. S. [UNESP]; Silva, Bruno P. [UNESP]; Sershen; Lima Neto, Milton C. [UNESP] (Elsevier B.V., 2019)
The last few decades have seen sustained research interest in the relationship between photoprotection and photoinhibition, but it is still unclear whether photoinhibition is a lasting form of photoprotection or consequence of undesirable photodamage under stress conditions such as salinity. Additionally, while photorespiration (P-R) is known to alter cellular redox balance by consuming reducing equivalents, the photoprotective role of P-R is controversial. Using the wild crop species (Ricinus communis) this study investigated the role of two key enzymes of the photorespiratory pathway (viz. catalase [CAT], and glycolate oxidase [GO]) in plant photoprotection and oxidative metabolism responses to salinity. The data show that in R. communis, P-R is an important photoprotective mechanism avoiding photoinhibition in plants under salinity. Suppressing the activity of GO disrupted the fine balance between the photosynthetic electron transport and the Calvin-Benson cycle reactions. Additionally, inhibiting GO, and by consequence P-R, led to decreases in the activation state and activity of Rubisco. Although the inhibition of GO in the absence of salinity decreased photosynthesis, other photoprotective mechanisms and the enzymatic and non-enzymatic antioxidant system remained functional. In contrast, inhibiting CAT activity triggered increasing H2O2 and O-2 center dot(-) in R. communis plants, irrespective of whether they were exposed to salinity or not. These findings are discussed in terms of the physiological importance of P-R in the acclimation of this wild crop species to salinity and its consequences on photosynthetic efficiency.
Keywords: Catalase; Glycolate oxidase; Photoprotective mechanism; Reactive oxygen species; Ricinus communis